EFFORTS TO INCREASE THE COMPETENCE OF PROSPECTIVE PHYSICS TEACHERS IN THE FACE OF THE MERDEKA BELAJAR CURRICULUM AT THE MADRASAH ALIYAH LEVEL - juita, dewi (Universitas PGRI Sumatera Barat, 2023)
This study aims to find out what efforts can be made by micro teaching lecturers in their lecture classes to increase the competence of prospective physics teachers and to determine the level of student satisfaction with the efforts made by micro teaching lecturers. . This study uses a quantitative and qualitative approach with descriptive methods. Quantitative descriptive method is used to present student satisfaction data in the form of percentages and then a qualitative approach is used to explain what efforts have been made by micro teaching lecturers for the students they teach. The sample in the study were 9 students who took the micro teaching course. This research resulted in several efforts that could be made by teachers in improving the competence of prospective physics teacher students, namely conducting material presentations related to the Merdeka Belajar curriculum material, providing instructions regarding how to make teaching modules along with examples, examples of learning videos in the Merdeka Belajar curriculum, and criticizing practice. Teach on an ongoing basis. The overall level of student satisfaction with the efforts made by lecturers in the micro teaching course is 83.33%. The most satisfying effort for students is the criticism given by supporting lecturers and colleagues on student teaching performances which are carried out three times in one semester.